Characterization and Evolution of Tetrameric Photosystem I from the Thermophilic Cyanobacterium Chroococcidiopsis sp TS-821 . Issue 3 (28th March 2014) - Li, Meng; Semchonok, Dmitry A.; Boekema, Egbert J.; Bruce, Barry D.
Abstract : This study characterizes a tetrameric/dimeric form of photosystem I (PSI) from the thermophilic cyanobacterium Chroococcidiopsis TS-821 and suggests that this PSI structure may be an intermediate during evolution to a monomeric form in plants. Abstract: Photosystem I (PSI ) is a reaction center associated with oxygenic photosynthesis. Unlike the monomeric reaction centers in green and purple bacteria, PSI forms trimeric complexes in most cyanobacteria with a 3-fold rotational symmetry that is primarily stabilized via adjacent PsaL subunits; however, in plants/algae, PSI is monomeric. In this study, we discovered a tetrameric form of PSI in the thermophilic cyanobacterium Chroococcidiopsis sp TS-821 (TS-821). In TS-821, PSI forms tetrameric and dimeric species. We investigated these species by Blue Native PAGE, Suc density gradient centrifugation, 77K fluorescence, circular dichroism, and single-particle analysis. Transmission electron microscopy analysis of native membranes confirms the presence of the tetrameric PSI structure prior to detergent solubilization. To investigate why TS-821 forms tetramers instead of trimers, we cloned and analyzed its psaL gene. Interestingly, this gene product contains a short insert between the second and third predicted transmembrane helices. Phylogenetic analysis based on PsaL protein sequences shows that TS-821 is closely related to heterocyst-forming cyanobacteria, some of which also have a tetrameric form of PSI . These results are discussed in light of chloroplast evolution, and we propose that PSI evolved stepwise from a trimeric form to tetrameric oligomer en route to becoming monomeric in plants/algae.